EFFECT OF ADRENALECTOMY ON REMISSION OF SUBCLINICAL LEFT VENTRICULAR DYSFUNCTION IN PATIENTS WITH PHEOCHROMOCYTOMA: A SPECKLE-TRACKING ECHOCARDIOGRAPHY STUDY. (April 2021) - Kvasnicka, Jan; Zelinka, Tomas; Petrak, Ondrej; Kratka, Zuzana; Indra, Tomas; Widimsky, Jiri
Abstract: Objective: Pheochromocytomas (PHEO) are tumors arising from chromaffin cells from the adrenal medulla, having the ability to produce, metabolize and secrete catecholamines. The overproduction of catecholamines leads by many mechanisms to the decline of longitudinal function of the left ventricle measured by speckle tracking echocardiography. Patients with PHEO have a lower magnitude of global longitudinal strain (GLS) than the patients with essential hypertension, although the ejection fraction of left ventricle (LV EF) remains in normal range. Design and method: We analysed 24 patients (14 females and 10 males) with recent diagnosis of PHEO and one year after adrenalectomy. We performed an echocardiographic examination including the evaluation of GLS by speckle tracking analysis. Results: One year after adrenalectomy magnitude of GLS increased (-14.3 ± 1.8 to -17.7 ± 1.6 %; p < 0.001), although values of LV EF remained unchanged (0.66 ± 0.07 vs. 0.65 ± 0.05; n.s.). In addition, there was also found a decrease in the indexed mass of the left ventricle (95.3 ± 18.7 to 83.6 ± 17.8 g/m2; p < 0.05). Conclusions: In patients with PHEO, adrenalectomy leads to an improvement of subclinical left ventricular dysfunction represented by increasing magnitude of GLS.